(untitled) (Cultura Económica, 2025)
This article offers a rereading of Giambattista Vico’s De nostri temporis studiorum ratione considering its relevance for contemporary philosophical education. Addressing the enduring tension between rationalism and humanism, critique and topics, it argues that Vico’s pedagogy articulates an integrative model of reason capable of overcoming dichotomies inherited from modern thought. The study situates Vico’s pedagogical project within its historical framework and examines modern receptions—by Gadamer, Grassi, and Hayden White—that reveal both the productivity and the limits of his legacy. Building on this discussion, it proposes an interpretation of Descartes’s Meditations on First Philosophy from a perspective that reconnects rhetoric, philosophy, and critique, following the insights of Vico’s approach. The article concludes that restoring the link between philosophy and rhetoric allows for a renewed understanding of philosophical education and of modern reason itself, opening a formative horizon in which critique, imagination, and a shared sense of community are brought into dialogue.